Inhibitor of caspase-activated DNase expression enhances caspase-activated DNase expression and inhibits oxidative stress-induced chromosome breaks at the mixed lineage leukaemia gene in nasopharyngeal carcinoma cells - Siaw, Shi Boon; Sim, S.P (BioMed Central, 2015)
Nasopharyngeal carcinoma (NPC) is commonly found in Asia, especially among the Chinese ethnic group. Chromosome rearrangements are common among NPC patients. Although the mechanism underlying the chromosome rearrangements in NPC is unclear, various mechanisms including activation of caspase-activated DNase (CAD) were proposed to contribute to chromosome rearrangements in leukaemia. Activation of CAD can be initiated by multiple agents, including oxidative stress, which is well implicated in carcinogenesis. CAD is the main enzyme that causes DNA fragmentation during apoptosis, and CAD is also implicated in promoting cell differentiation. In view of the role of oxidative stress in carcinogenesis and CAD activation, and since CAD was suggested to contribute to chromosome rearrangement in leukaemia, we hypothesise that oxidative stress-induced CAD activation could be one of the mechanisms that leads to chromosome rearrangements in NPC.